Reconceptualization of school readiness: neoliberal paradigm and privatization in early childhood education - Regita, Regita Musfita; Azhar, Aghnia Farrassyania; Nurcahyani, Ratna Dwi; Rizkita, Diantifani (IKIP Siliwangi, 2024)
Privatization and neoliberalism have significantly impacted educational policies, exacerbating inequalities in access to education, particularly for children from low-socioeconomic backgrounds. This study investigated the effects of these policies on access, quality, and character development at TK Cendani, Bandung. Employing a qualitative case study approach, data were collected through observation and interviews and analyzed using Grounded Theory. The findings revealed a paradoxical interplay between inclusivity and exclusivity within the education system. Children from disadvantaged backgrounds were often denied equitable opportunities, leading to discriminatory practices that hindered their development. Teachers' needs frequently took precedence over students', resulting in an imbalanced teaching and learning environment. Moreover, the proliferation of elite schools accessible only to children from affluent families further exacerbated educational disparities. These results underscore the necessity for a more inclusive educational policy that harmonizes academic achievement with the development of children's character.